RELASI ISLAM DAN KEBEBASAN: TELAAH ATAS PEMIKIRAN ULIL ABSHAR ABDALLA - Taufani Taufani (Jurnal Dakwah Tabligh, 2016)
This writing focuses on Ulil Abshar Abdallah's thoughts on the relation of freedom and Islam. The purpose of this paper is to find out how Ulil Abshar Abdallah regards the freedom that is related to the Islamic’s perpective which has been seen as the alien with the view of freedom. This method of writing is done by using a qualitative approach and the analysis model is descriptive analysis. The existing data is collected by library research by reading the literatures related to Ulil Abshar Abdalla’s thoughts. The results of this paper explains that the freedom for Indonesian society is contrary to the teachings of Islam because they still interpret the teachings are limited to the text. the worship of Islamic texts is still very strong in the life of Indonesian society in general. This outward attitude of dogmatism can be pursued by recontextualizing interpretations that are in line with the real development of humanity today.